Open-End Organizational Structures and Limits to Arbitrage - Giannetti, Mariassunta; Kahraman, Bige (Review of Financial Studies, 2018)
We provide evidence that open-end organizational structures undermine incentives for asset managers to attack long-term mispricing. We compare open-end funds with closed-end funds. Closed-end funds purchase more underpriced stocks than do open-end funds, especially if the stocks involve high arbitrage risk. We then show that hedge funds with high share restrictions having a lower degree of open-endedness also trade against longterm mispricing to a larger extent than do other hedge funds. Our analysis suggests that open-end organizational structures are not conducive to long-term risky arbitrage.